Consumer Attitudes and Concerns about Beef Consumption in Argentina and Other South American Countries - Bifaretti, Adrián (2023)
In South America, modifications in beef consumption habits, mainly related to economic reasons, new lifestyles, and new eating behaviors, are being observed. If this trend continues, beef consumption could continue to fall or there would be a greater share of cheaper types of meat. In general, consumer concerns related to health, animal welfare, and environmental impact are increasing. Most of the population in South America follows an omnivorous diet, with a minority of vegetarians/vegans. In Argentina, around 30% consider themselves as flexitarians and around 5% as vegetarians/vegans, with centennials and millennials being the ones that mostly follow these types of behaviors. For flexitarians, the main reason that leads them to adopt this diet is the search for healthier eating. In general, consumers consider livestock production to be a sustainable activity; although, ethical concerns are growing among the younger generations. Finally, around 30% of the total population is willing to partially replace the consumption of beef to avoid animal slaughter and 8% would abandon it for this reason. The current trend would indicate that, if the conditions defined by the present scenarios continue, the motivations to consume less beef could be strengthened.